The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12051894
|View full text |Cite
|
Sign up to set email alerts
|

New Policy Approaches for Increasing Response to Climate Change in Small Rural Municipalities

Abstract: Although nearly half of the world population lives in rural small municipalities, research on climate change policy at this level is widely neglected. Frequently climate change adaptation is not a policy field in these small municipalities, which is both a problem and a risk. This paper aims at analyzing the climate policy of small and medium-sized local authorities with specific focus on adaptation. It presents results from a comprehensive survey among approximately 400 small municipalities in Bavaria, German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 65 publications
2
28
0
3
Order By: Relevance
“…The polarization of socioeconomic activities in line with urban agglomeration impacts population mobility and circular migration. Furthermore, the effect of population mobility, of "chasing" in low urbanisation areas, is greater than the effects of agglomeration in high urbanisation areas, which promotes sustainable convergence of urbanisation between regions (Bausch & Koziol, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The polarization of socioeconomic activities in line with urban agglomeration impacts population mobility and circular migration. Furthermore, the effect of population mobility, of "chasing" in low urbanisation areas, is greater than the effects of agglomeration in high urbanisation areas, which promotes sustainable convergence of urbanisation between regions (Bausch & Koziol, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives typically see knowledge exchange as one of their core missions (see Box 1). In Germany, Bausch and Koziol (2020) found that participation in municipal networks was one of the…”
Section: Interestsmentioning
confidence: 99%
“…For instance, the United Nations Framework Convention on Climate Change (UNFCCC) and its 2015 Paris Agreement “rel[y] on soft instruments and mechanisms, such as learning and mimicry, and so seek […] a gradual diffusion of adaptation across space and time” (Lesnikowski et al, 2017, p. 828). Many scholars have indeed begun to detect evidence of the growing spread of adaptation policies at various levels of governance, including the municipal level (Aguiar et al, 2018; Bausch & Koziol, 2020; Hunt & Watkiss, 2011; Otto et al, 2021; Reckien et al, 2014), the subnational or state level (Rai, 2020), the national level (Massey et al, 2014), the international level (Dellmuth & Gustafsson, 2021; Remling, 2018), and combinations thereof (Tompkins et al, 2010). In so doing, adaptation scholarship frequently engages with the established diffusion mechanisms implicitly and partially, rather than explicitly and systematically with support of the available theoretical diffusion perspectives—a gap that we begin to address with this review.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends in revitalization policies take into account the need to apply naturebased solutions [70][71][72][73][74][75][76][77][78], as critical components of sustainability transitions [71], climate change mitigation, and adaptation strategies [79][80][81][82][83][84], important also for small municipalities [85][86][87][88][89][90]. The benefits of nature-based solutions are still not recognized enough in urban planning policies of cities [74].…”
Section: Literature Review 21 Revitalization Of Small Towns and Thementioning
confidence: 99%